2017
DOI: 10.1186/s13005-017-0151-3
|View full text |Cite
|
Sign up to set email alerts
|

A new concept for implant-borne dental rehabilitation; how to overcome the biological weak-spot of conventional dental implants?

Abstract: BackgroundEvery endosseous dental implant is dependent on an adequate amount and quality of peri-implant hard and soft tissues and their fully functional interaction. The dental implant could fail in cases of insufficient bone and soft tissues or due to a violation of the soft to hard tissues to implant shoulder interface with arising of a secondary bone loss.MethodTo overcome this biological weak-spot, we designed a new implant that allows for multi vector endosseous anchorage around the individual underlying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 20 publications
(15 reference statements)
0
23
0
7
Order By: Relevance
“…Recent study on custom‐designed bone implants has mainly focuses on dentures or teeth, maxillary or mandible, and femurs. Other notable implant types include those for the humerus, the cranium/skull, and the tibia …”
Section: Features Of Customized Bone Implant Devicesmentioning
confidence: 99%
“…Recent study on custom‐designed bone implants has mainly focuses on dentures or teeth, maxillary or mandible, and femurs. Other notable implant types include those for the humerus, the cranium/skull, and the tibia …”
Section: Features Of Customized Bone Implant Devicesmentioning
confidence: 99%
“…We must mention a technique recently published by Gellrich et al which consists of the accomplishment of a treatment strategy through the installation of subperiosteal implants through a rigid fixation anchorage system. 31,32 This type of treatment, known as IPS-Dental, aims at the execution of customized connections for patients who go against the characteristics of traditional implantology and can be used in cases of AM and patients with a history of extensive bone defects, such as post treatment of oral cancer. Therefore, it is a promising technique for the minimally invasive rehabilitation, with reduction in costs and treatment time and in accordance with the concepts of modern implantology.…”
Section: Discussionmentioning
confidence: 99%
“…Since few cases with a short follow-up time have been published, in addition to not having a specific protocol or indication for these types of patients, this technique was not initially included in the AM rehabilitation protocol. 31,32 All clinical cases of severe mandibular atrophy are currently addressed by all oral and maxillofacial surgeons linked to our service for over 10 years, using the approaches suggested in this study. We may now consider that our complications associated with the therapeutic approaches employed in severely AM are close to zero.…”
Section: Discussionmentioning
confidence: 99%
“…Research and industry concerns lie in determining where AM can substitute or generate new manufacturing systems. [53][54][55] AM technologies have been selected to manufacture Ti implants, customized subperiosteal Ti implants, [82][83][84][85][86] customized AM Ti meshes for bone grafting techniques, [87][88][89][90][91][92][93][94][95] Co-Co frameworks for implant impression procedures, 96,97 and Co-Cr and Ti implant frameworks for implant-supported prostheses. [98][99][100][101][102] With the introduction of AM technologies, different studies have analyzed the potential to manufacture Ti AM dental implants (Table 1), [55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73] customized designs that replicate the tooth's root shape (Table 2), [74]…”
Section: Application Of Am Technologies In Implant Dentistrymentioning
confidence: 99%
“…Several studies clinically evaluated AM subperiosteal implants (Table 3). [82][83][84][85][86] Cerea and Dolcini 83 performed a retrospective clinical study on the survival and complication rates of customized subperiosteal AM Ti implants in 70 patients with 2 years of follow-up. Authors reported 98% implant survival rate, 1.4% biological complications rate, and an 8.9% prosthetic complication rate.…”
Section: Application Of Am Technologies In Implant Dentistrymentioning
confidence: 99%